Establishment and systematic characterization of Mycobacterium tuberculosis in bioreactors - Knabenbauer, Phillip, author; Dobos, Karen, advisor; Slayden, Richard, committee member; McNeil, Michael, committee member; Peebles, Christie, committee member (Colorado State University. Libraries, 2016)
Mycobacterium tuberculosis infection is characterized by active and latent disease states. Granuloma-induced oxygen tension may shift bacteria into bacteriostatic persistence. Current models of hypoxia-induced mycobacteria have limitations, requiring establishment of novel culturing methods. Here, M. tuberculosis was propagated under defined oxygen concentration in bioreactors. Initial analyses confirmed mycobacterial non-replicating persistence. This study will provide insight into core physiological adaptations of M. tuberculosis while reducing bias from the contaminants during adaptation into dormancy. Here we describe a novel method of propagation using defined oxygen concentrations, then enrich the final culture for viability to remove transcriptional bias, and finally interrogate the presence of viable but non-culturable tubercle bacilli in order to obtain a greater sense of true viability. The current study will further contribute to our understanding of the physical adaptation of Mtb during growth and dormancy, by removing bias from the contaminating transcriptome gradient generated by the temporal adaptation of M. tuberculosis into dormancy. This will enhance the accuracy of downstream structural and transcriptomic analyses as well as give rise to a novel high throughput approach to M. tuberculosis propagation for research materials.